Effects of Curcumin in a Mouse Model of Very High Fat Diet-Induced Obesity - Iurii Koboziev; Shane Scoggin; Xiaoxia Gong; Parvin Mirzaei; Masoud Zabet-Moghaddam; Mohammad Yosofvand; Hanna Moussa; Yava Jones-Hall; Naima Moustaid-Moussa (Biomolecules, 2020)
Worldwide rates of Western-diet-induced obesity epidemics are growing dramatically. Being linked with numerous comorbidities and complications, including cardiovascular disease, type 2 diabetes, cancer, chronic inflammation, and osteoarthritis (OA), obesity represents one of the most threatening challenges for modern healthcare. Mouse models are an invaluable tool for investigating the effects of diets and their bioactive components against high fat diet (HFD)-induced obesity and its comorbidities. During recent years, very high fat diets (VHFDs), providing 58–60% kcal fat, have become a popular alternative to more traditional HFDs, providing 40–45% total kcal fat, due to the faster induction of obesity and stronger metabolic responses. This project aims to investigate if the 60% fat VHFD is suitable to evaluate the protective effects of curcumin in diet-induced obesity and osteoarthritis. B6 male mice, prone to diet-induced metabolic dysfunction, were supplemented with VHFD without or with curcumin for 13 weeks. Under these experimental conditions, feeding mice a VHFD for 13 weeks did not result in expected robust manifestations of the targeted pathophysiologic conditions. Supplementing the diet with curcumin, in turn, protected the animals against obesity without significant changes in white adipocyte size, glucose clearance, and knee cartilage integrity. Additional research is needed to optimize diet composition, curcumin dosage, and duration of dietary interventions to establish the VHFD-induced obesity for evaluating the effects of curcumin on metabolic dysfunctions related to obesity and osteoarthritis.